2022
DOI: 10.3389/fmicb.2022.1003783
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological characteristics and molecular evolution mechanisms of carbapenem-resistant hypervirulent Klebsiella pneumoniae

Abstract: Carbapenem-resistant hypervirulent Klebsiella pneumoniae (CR-hvKP), a type of Klebsiella pneumoniae (KP) that exhibits hypervirulence and carbapenem resistance phenotypes, can cause severe infections, both hospital- and community-acquired infections. CR-hvKP has brought great challenges to global public health and is associated with significant morbidity and mortality. There are many mechanisms responsible for the evolution of the hypervirulence and carbapenem resistance phenotypes, such as the horizontal tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 146 publications
0
34
0
Order By: Relevance
“…SPs can acquire iron from the binding protein in the host body and can then bind to the receptor to re-enter cells. Four SPs secreted by hvKP, namely salmochelin, enterobactin, yersiniabactin, and aerobactin, have been reported previously ( Chen et al., 2018 ; Han et al., 2022 ). The function of aerobactin gene iutA is well-correlated with the ex vivo growth/survival of hvKP in humans ( Russo et al., 2015 ).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…SPs can acquire iron from the binding protein in the host body and can then bind to the receptor to re-enter cells. Four SPs secreted by hvKP, namely salmochelin, enterobactin, yersiniabactin, and aerobactin, have been reported previously ( Chen et al., 2018 ; Han et al., 2022 ). The function of aerobactin gene iutA is well-correlated with the ex vivo growth/survival of hvKP in humans ( Russo et al., 2015 ).…”
Section: Discussionmentioning
confidence: 84%
“…Most of the carbapenem-resistant HMKP isolates were associated with significant risk factors such as prior antibiotic therapy, previous hospitalization for 5 days or more, invasive procedures, and mechanical ventilation. Other studies have reported that prolonged hospitalization, invasive procedures (e.g., central or urinary catheter insertion, tracheostomy, and invasive abdominal procedures), serious underlying diseases (e.g., diabetes mellitus, hemiplegia, and solid tumors), and prior carbapenem exposure, were independent predictors for infection development in patients with carbapenem-resistant HMKP isolates ( Borer et al., 2012 ; Chen et al., 2018 ; Han et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This hybrid plasmid has a large size (~326 Kb) and was formed as a result of an unknown event of recombination. In recent years, many studies have reported carbapenem-resistant hypervirulent K. pneumoniae (CR-hvKP) [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, many studies have reported the evolution of K. pneumoniae into carbapenem-resistant hypervirulent K. pneumoniae (CR-hvKP) via the acquisition of hybrid plasmids. Many variants of Vir-KPC plasmids have been described to date in different regions [ 23 ]. Emergence of hybrid resistance and virulence plasmids harboring ND metallo-beta-lactamase in K. pneumoniae of different STs (ST15, ST147, ST395, and ST874) has been reported in Russia [ 24 ].…”
Section: Introductionmentioning
confidence: 99%